Barriers to and Facilitators of Help-Seeking Behavior Among Men Who Experience Sexual Violence. Issue 2 (March 2018) - Donne, Martina Delle; DeLuca, Joseph; Pleskach, Pavel; Bromson, Christopher; Mosley, Marcus P.; Perez, Edward T.; Mathews, Shibin G.; Stephenson, Rob; Frye, Victoria
Research on sexual violence and related support services access has mainly focused on female victims; there is still a remarkable lack of research on men who experience sexual violence. Research demonstrates that people who both self-identify as men and are members of sexual-orientation minority populations are at higher risk of sexual violence. They are also less likely to either report or seek support services related to such experiences. The present study is an exploratory one aimed at filling the gap in the literature and better understanding how men, both straight and gay as well as cisgender and transgender, conceptualize, understand, and seek help related to sexual violence. A sample of 32 men was recruited on-line and participated in either a one-on-one in-depth interview ( N = 19) or one of two focus group discussions ( N = 13). All interviews and groups were audiotaped, professionally transcribed and coded using NVivo 9 qualitative software. The present analysis focused on barriers to and facilitators of support service access. Emergent and cross-cutting themes were identified and presented, with an emphasis on understanding what factors may prevent disclosure of a sexual violence experience and facilitate seeking support services and/or professional help. Through this analysis, the research team aims to add knowledge to inform the development of tools to increase service access and receipt, for use by both researchers and service professionals. Although this study contributes to the understanding of the issue of men's experiences of sexual violence, more research with diverse populations is needed.